2015
DOI: 10.1097/apo.0000000000000058
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Central Corneal Thickness of Primary Angle Closure and Primary Angle Closure Glaucoma and Its Effect on Visual Field Progression

Abstract: The PAC and PACG had statistically significant thinner CCT compared with the controls. Thin CCT was associated with visual field progression based on the mean AGIS score in PACG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Confusingly, patients with primary angle closure (PAC) or PAC glaucoma have been reported with thinner CCT compared with controls (range: 509.7 ± 27.4 to 525.9 ± 5.0 µm) [41,49]. Kniestedt et al found no association in their cohort [36].…”
Section: Glaucomamentioning
confidence: 96%
“…Confusingly, patients with primary angle closure (PAC) or PAC glaucoma have been reported with thinner CCT compared with controls (range: 509.7 ± 27.4 to 525.9 ± 5.0 µm) [41,49]. Kniestedt et al found no association in their cohort [36].…”
Section: Glaucomamentioning
confidence: 96%
“…In addition, further research is also needed to explore other factors that may influence CCT in glaucoma patients, such as genetic factors, race, and the use of certain medications. A better understanding of these factors may aid in the development of more effective glaucoma prevention and treatment strategies [18][19][20].…”
mentioning
confidence: 99%